2021
DOI: 10.1186/s13690-021-00752-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternity waiting home as a potential intervention for reducing the maternal mortality ratio in El Salvador: an observational case study

Abstract: Background El Salvador is recognized as a country that has effectively reduced its Maternal Mortality Ratio (MMR). While health indicators, such as total fertility rate, adolescent fertility rate, skilled birth attendance, and health expenditures, have improved in El Salvador, this improvement was unremarkable compared to advancements in other developing countries. How El Salvador could achieve an outstanding decrease in MMR despite unexceptional improvements in health and non-health indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The Birth Waiting Home Program is expected to reduce the number of maternal deaths, increase coverage of deliveries by health workers and at the same time increase coverage of deliveries in health service facilities and adequate emergency services. Several studies have shown that RTK can prevent maternal deaths in remote areas by increasing access to health care facilities and reducing perinatal deaths (Yoon & Kim, 2021); (Zuanna et al, 2021); (Tiruneh et al, 2019).…”
Section: Environmental Factormentioning
confidence: 99%
“…The Birth Waiting Home Program is expected to reduce the number of maternal deaths, increase coverage of deliveries by health workers and at the same time increase coverage of deliveries in health service facilities and adequate emergency services. Several studies have shown that RTK can prevent maternal deaths in remote areas by increasing access to health care facilities and reducing perinatal deaths (Yoon & Kim, 2021); (Zuanna et al, 2021); (Tiruneh et al, 2019).…”
Section: Environmental Factormentioning
confidence: 99%